Sacrificial MOF-derived MnNi hydroxide for high energy storage supercapacitor electrodes via DFT-based quantum capacitance study - Elahe Torabi; Amir Kazemi; Mohsen Tamtaji; Faranak Manteghi; Sohrab Rohani; William A. Goddard (Heliyon)
Electrochemical energy storage plays a critical role in the transition to clean energy. With the growing demand for efficient and sustainable energy solutions, supercapacitors have gained significant attention due to their high specific capacitance, rapid charge/discharge capabilities, long lifespan, safe operation across various temperatures, and minimal maintenance needs. This study introduces a novel approach for the synthesis of high-performance supercapacitor electrodes by using MnNi-MOF-74 as a precursor. Bimetallic Mn(OH)₂/Ni(OH)₂ hydroxides (MnNi-x, where x = 2, 6, 12) with tailored morphologies were successfully fabricated by treating MnNi-MOF-74 anchored on nickel foam with different concentrations of KOH. Among the various synthesized samples, MnNi-6 exhibited the best performance, with a remarkable specific capacitance of 4031.51 mF cm⁻2 at 2 mA cm⁻2, attributed to its high surface area of 186 m2/g, optimized particle size, and abundant micropores. Furthermore, MnNi-6 demonstrated exceptional thermal stability, positioning it as a promising candidate for high-temperature supercapacitors. It also exhibited excellent cycling stability, retaining 86.34 % of its capacity after 10,000 cycles at 10 mA cm⁻2, highlighting its remarkable durability. Density functional theory (DFT) calculations were conducted to explore the quantum capacitance of the bimetallic hydroxide. The DFT results revealed electron density near the Fermi level, which directly contributes to the high quantum capacitance of Mn(OH)₂/Ni(OH)₂ with a Mn:Ni molar ratio of 3:1. This work underscores the potential of MOF-derived materials as a promising route for the development of high-performance supercapacitor electrodes, paving the way for future advances in electrochemical energy storage technologies.